Knowledge domain and hotspots concerning photosensitive hydrogels for tissue engineering applications: A bibliometric and visualized analysis (1996-2022) - Fu, Hongxun; Wang, Hao; Jiang, Lin; Zhang, Yupeng; Tong, Haibin; Meng, Guixian; Sun, Meiyan (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: The aim of tissue engineering (TE) is to replace the damaged tissues or failed organs, or restore their missing functions. The important means to achieve this aim is to integrate biomaterials and life elements. Hydrogels are very attractive biomaterials in the field of TE. In particular, engineering extracellular matrices (ECMs) formed by photosensitive hydrogels have captivated much attention, because photopolymerization has many advantages over traditional polymerization approaches, such as rapidity of reaction, spatiotemporal controllability of polymerization process, and operability at physiological temperature, especially it can realize the fabrications of engineering ECMs in the presence of living cells. There have been many excellent reviews on the applications of photosensitive hydrogels in TE in recent years, however, it is inevitable that researchers may have left out many important facts due to exploring the literature from one or a few aspects. It is also a great challenge for researchers to explore the internal relationships among countries, institutions, authors, and references from a large number of literatures in related fields. Therefore, bibliometrics may be a powerful tool to solve the above problems. A bibliometric and visualized analysis of publications concerning the photosensitive hydrogels for TE applications was performed, and the knowledge domain, research hotspots and frontiers in this topic were identified according to the analysis results. Methods: We identified and retrieved the publications regarding the photosensitive hydrogels for TE applications between 1996 and 2022 from Web of Science Core Collection (WoSCC). Bibliometric and visualized analysis employing CiteSpace software and R-language package Bibliometrix were performed in this study. Results: 778 publications meeting the eligibility criteria were identified and retrieved from WoSCC. Among those, 2844 authors worldwide participated in the studies in this field, accompanied by an average annual article growth rate of 15.35%. The articles were co-authored by 800 institutions from 46 countries/regions, and the United States published the most, followed by China and South Korea. As the two countries that published the most papers, the United States and China could further strengthen cooperation in this field. Univ Colorado published the most articles (n = 150), accounting for 19.28% of the total. The articles were distributed in 112 journals, among which Biomaterials (n = 66) published the most articles, followed by Acta Biomaterialia (n = 54) and Journal of Biomedical Materials Research Part A (n = 42). The top 10 journals published 47.8% of the 778 articles. The most prolific author was Anseth K (n = 33), followed by Khademhosseini A (n = 29) and Bryant S (n = 22). A total of 1443 keywords were extracted from the 778 articles and the keyword with the highest centrality was “extracellular matrix” (centrality: 0.12). The keywords appeared recently with strong citation bursts were “gelatin”, “3d printing” and “3d bioprinting”, representing the current research hotspots in this field. “Gelma”, “3d printing” and “thiol-ene” were the research frontiers in recent years. Conclusion: This bibliometric and visualized study offered a comprehensive understanding of publications regarding the photosensitive hydrogels for TE applications from 1996 to 2022, including the knowledge domain, research hotspots and frontiers in this filed. The outcome of this study would provide insights for scholars in the related research filed.